Alkaline cleaning-in-place of pink guava puree fouling deposit using lab-scale cleaning test rig - Khalid, Nurul Izzah; Ab. Aziz, Norashikin; Abdul Aziz, Nuraini; Taip, Farah Saleena; Anuar, Mohd Shamsul (Elsevier, 2014)
Cleaning-in-place (CIP) of pink guava puree (PGP) fouling deposits is not well known compared to dairy deposits which is well established. Lab-scale cleaning test rig has been used to investigate the cleaning performance of PGP deposits. Removal mechanism during alkaline-based cleaning of PGP deposits were investigated using NaOH concentrations (1.0 wt% -2.0 wt%), temperatures (35 - 70 °C) and fluid velocities (0.6-1.5m/s) over a range of Reynolds number (Re= 4x104 - 1.8x105). Cleaning rate was quantified by measuring the remaining area of the deposits at sample holder at every 1 min. The efficient CIP process for PGP fouling deposit can be obtained at 1.5m/s, 70 °C, with concentration of (1.0 - 2.0wt%).